NAVIGATING LEADERSHIP TRANSITIONS: THE CHALLENGES AND IMPLICATIONS OF INTERIM AUTHORITY IN INDONESIAS REGIONAL GOVERNANCE - Arifin, Firdaus; Farma, Mella Ismelina; Maarif, Ihsanul; Murbani, Anastasia Wahyu; Prihartanto, Yudi (Universitas Syiah Kuala, 2025)
The limitations placed on the authority of interim Regional Heads, as outlined in Indonesian Law Number 23 of 2014 on Regional Governance, present significant challenges to the continuity of strategic decision-making during leadership transitions. The ambiguity surrounding the scope of interim authority often results in stagnation in public policy implementation, adversely impacting regional development and governance. This study examines the philosophical underpinnings and legal foundations of interim authority, while also evaluating the tangible effects of these limitations on the functioning of regional government. Utilizing a normative legal methodology that incorporates both statutory and conceptual approaches, this research is grounded in a thorough review of primary and secondary legal sources. The findings indicate that interim authority should be viewed as a constitutional mandate designed to ensure the seamless operation of government, despite its temporary nature. However, in practice, stringent normative constraints can lead to a significant leadership vacuum and create opportunities for political interference. These findings underscore the necessity for regulatory reform that provides interim Regional Heads with appropriate flexibility in making strategic decisions, all while maintaining the principles of accountability and oversight. Such policy reforms are essential for sustaining an effective and responsive regional government in the face of political dynamics and leadership transitions.